Are TEFL vs. Non-TEFL Graduates Teachers’ Experience, Creativity, Mindfulness, and Instructional Competency Different ? Experience, Sense of Creativity, Mindfulness, and Instructional Competency - Faravani, Akram; Tohidifar, Fatemeh (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
Recent advancement in educational systems has fostered the significance of language teachers’ responsibilities to improve their qualities and competencies since students’ development is directly related to teachers’ qualities and profession. The current study aims at finding the interrelationships between TEFL graduates vs. Non-TEFL graduate's EFL teachers’ Teaching Experience, Sense of Creativity, Sense of Mindfulness, and Instructional Competency. 318 EFL teachers were selected through convenience sampling from different institutes. Participants filled out three questionnaires Teaching Creativity Quotient, Five Facet Mindfulness Questionnaire, and Instructional Competency Questionnaire by using both paper-based and online methods. To analyze the data, two models for interrelationships among the variables of the study for the two groups of TEFL and Non- TEFL graduates were proposed and tested using path analysis. The findings showed that the proposed model in the TEFL group perfectly fit the data. In the non-TEFL group, the goodness of fit indices was not within the acceptable range. Moreover, there was a significant difference between the two groups (TEFL and Non-TEFL teachers) regarding instructional competency. This study can be beneficial for teachers, learners, and supervisors.